Estudio de factibilidad para la creación de una empresa productora y comercializadora de semen bovino con mercado internacional (2015)
This draft grade report on the feasibility and the opportunity to exploit the international market in the production and marketing of bovine semen from Brahman, this is a product that has been commercialized about half a decade ago; which is developed by animal reproductive biotechnologies that exist nowadays. Its main objective is to increase breeding livestock population scale, short-term by the process of artificial insemination. The project will address a number of studies, starting with the socio-economic study that will reveal the economic and social environment where the project is located, represented indicators as PIB, inflation, unemployment, among others. A study of international market which will be released in the target demand, potential customers, competitors, marketing and product price market also performed. The technical study will determine the process, size and annual production capacity of bovine semen to cover the demand, too, the macro and micro location of the project. Likewise, it held an organizational, environmental and legal study enclosing the organization of the company, the manual processes and functions, protection standards and environmental impact by the project implementation and in the legal framework, the project was established as an international trading legal form, tax and hiring. The financial study will reveal the investment amount for the implementation of the project, the cost of production and sales, the balance sheet, income statements and cash flow; all it designed to five years where the results will be analyzed to determine the feasibility of the project. The respective conclusions and recommendations for the project will be made to determine if it is feasible or not, from a socioeconomic point of view, marketing, technical, organizational, legal, environmental and financial.